The Mucolipin-1 (TRPML1) Ion Channel, Transmembrane-163 (TMEM163) Protein, and Lysosomal Zinc Handling - Cuajungco, Math P. (Front Biosci (Landmark Ed), 2017)
Lysosomes are emerging as important players in cellular zinc ion (Zn(2+)) homeostasis. The series of work on Zn(2+) accumulation in the neuronal lysosomes and the mounting evidence on the role of lysosomal Zn(2+) in cell death during mammary gland involution set a biological precedent for the central role of the lysosomes in cellular Zn(2+) handling. Such a role appears to involve cytoprotection on the one hand, and cell death on the other. The recent series of work began to identify the molecular determinants of the lysosomal Zn(2+) handling. In addition to zinc transporters (ZnT) of the solute-carrier family type 30A (SLC30A), the lysosomal ion channel TRPML1 and the poorly understood novel transporter TMEM163 have been shown to play a role in the Zn(2+) uptake by the lysosomes. In this review, we summarize the current knowledge on molecular determinants of the lysosomal Zn(2+) handling, uptake, and release pathways, as well as discuss their possible roles in health and disease.